Analysis of Work Environment, Job Training and Career Development on the Performance of District Court Employees in the Jurisdiction of the High Court with Job Satisfaction as a Mediating Variable - Saputra, Heru; Utomo, Kabul Wahyu; Rahayu, Heffi Christya (Borong Newinera Publisher, 2025)
The purpose of this study is to prove the significant direct influence of work environment variables, training, career development on employee performance and job satisfaction and to prove the significant indirect influence through mediation of job satisfaction between work environment, training, and career development on employee performance. This study was conducted on employees of the District Court Office in the Riau High Court jurisdiction with a population of all employees of the District Court in the Riau High Court jurisdiction totaling 215 people. The number of samples taken was 138 people where the sampling technique was carried out using probability sampling. The independent variables are work environment (X1), training (X2) and career development (X3), the mediating variable is job satisfaction (Z) and the dependent variable is employee performance (Y). The research data were analyzed using the Structural Equation Model-Partial Least Square (SEM-PLS) method with measurements using a Likert scale. The direct influence hypothesis test obtained a positive and insignificant influence between training (X1) on employee performance (Y), then a positive and significant influence between training (X2), career development (X3), and job satisfaction (Z) on employee performance (Y) and the work environment (X1), training (X2) and career development (X3) had a positive and significant influence on job satisfaction (Z). The indirect influence hypothesis test obtained a positive and significant influence between the work environment variable (X1), job training variable (X2), and career development (X3) on employee performance (Y) mediated by job satisfaction (Z).